Current status of cardiovascular health among US adults using the American heart association’s new “life’s essential 8”: Results from the National health and nutrition examination survey, 2017–2023 - Jiangtao Li; Xiang Wei (American Journal of Preventive Cardiology)
Background: The American Heart Association has recently updated its definition of what constitutes cardiovascular health (CVH), known as Life’s Essential 8 (LE8). This study evaluated the current status of CVH in US adults using the LE8 score and compared the overall CVH and each CVH metric between the pre-COVID-19 era and the COVID-19 era. Methods: Participants aged 20 to 79 years without a history of cardiovascular disease in the National Health and Nutrition Examination Survey (NHANES) cycles from 2017 to 2023 were included. The LE8 score and its components were analyzed in the entire population and further categorized by gender, age, race/ethnicity, education, household poverty, and depression. CVH scores were also assessed between the pre-COVID-19 era and the COVID-19 era. Sample weights and design were incorporated to calculate prevalence estimates and standard errors using standard survey procedures. Results: Among 11,939 adults, representing approximately 207,742,565 US adults, the mean overall CVH score was 68.5 (95 % CI, 67.6–69.4). Significant differences in mean overall CVH scores were observed by gender (women: 69.8; men: 67.2) and age groups (20–44 years: 72.1; 45–64 years: 65.5; 65–79 years: 65.2). Overall CVH scores were highest among non-Hispanic (NH) Asian (75.2) individuals, followed by NH White (69.0), other Hispanic (68.4), Mexican (67.6), and NH Black (64.6). Diet, physical activity, and body mass index had the lowest mean scores, while sleep health and blood glucose had the highest. Substantial differences in mean scores across demographic groups were observed for body mass index (range, 49.4–78.5), blood glucose (range, 73.4–92.4), and blood pressure (range, 55.4–82.2). Overall mean CVH scores significantly improved during the COVID-19 era (70.2 vs. 68.9) compared to the pre-COVID-19 era, primarily driven by increased scores on physical activity (72.8 vs. 52.4) and nicotine exposure (74.4 vs. 70.2). The prevalence of high CVH was significantly higher during the COVID-19 era compared to the pre-COVID-19 era (26.7 % vs. 22.2 %), while the prevalence of low CVH was decreased (7.6 % vs. 13.6 %). Conclusion: Despite improvements during the COVID-19 era, overall CVH among US adults remains suboptimal. Future research should prioritize interventions aimed at enhancing the CVH of the US population.